Synthesis of managerial fairness and its effects on perceived leader quality: the case of nationalised commercial banks of Bangladesh - Haq, Mahmudul; Jahangir, Nadim; Ahsan, Ali (© 2005 D. U. Journal of Marketing, 2017)
This article was published in the D. U. Journal of Marketing [ @ 2005 D. U. Journal of Marketing. ]